Driving the Research Integrity Message through Whiteboard Explainer Video Animation - Dr. Chiedozie Ike (My University, 2025)
This webinar presentation explores how video animation can be used as a powerful medium to communicate research integrity and ethics in engaging, relatable, and creative ways. Featuring the work of Chiedozie Ike, the session showcases how tools like Instadoddle and Voomly are being applied in classrooms, webinars, and other campaigns to bring complex ethical concepts to life.
Keywords: Research Integrity; Research Ethics; Scholarly Education; OER